REDEFINING INDONESIA’S NATIONAL SECURITY IN ENSURING THE SURVIVAL OF THE NATION - Triswan Larosa (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2019)
Indonesia’s national security is still in debate since the separation of TNI-Polri’s functions and is more likely to be interpreted as national security and order (kamtibmas)’s effort. Meanwhile, in several states in the world, national security emphasis more on a holistic approach. This study provides a point of view to redefine Indonesia's national security to be more holistic and comprehensive, using the analytical framework of Security Vortex. So that, Indonesia's national security is a national policy that has the goal of ensuring the life and death of the Indonesia nation-state in the aspects of international security, state security and civil security, with three basic capabilities that must build, namely knowledge-based security, skill-based security, and rules-based security.